THE MEDIATING ROLE OF EMPLOYEE SATISFACTION IN THE RELATIONSHIP BETWEEN HUMAN RESOURCE PRACTICES AND TOURIST SATISFACTION: EVIDENCE FROM LEBANON'S TOURISM SECTOR - Ahmad El ZEIN; Lord Alex CARLILE; Cynthia Al ASMAR (Geo Journal of Tourism and Geosites)
The study aims to highlight the critical role of HR practice in shaping tourist experience and satisfaction, ultimately contributing to the success and reputation of tourism enterprises. Additionally, it aims to understand how eff ective HR management influences the overall experience and satisfaction of tourists. Using a mixed-methods approach, data was collected from 112 employees and tourists in Lebanese resorts. Structural Equation Modelling revealed significant relationships between HRP and employee satisfaction and performance. Employee satisfaction strongly correlated with tourist satisfaction, while employee performance showed a weaker correlation. Notably, tourists prioritized employee friendliness over professional expertise. This study contributes to the literature by highlighting the importance of employee attitude in shaping tourist experience in a developing country context. The findings have implications for HR strategies in the tourism industry, emphasizing the need to focus on fostering positive employee attitudes alongside professional skills.